Cocatalyst-controlled divergent cascade cycloaddition reaction of arylalkynols and dioxopyrrolidienes: access to spiroketals and oxa-bridged eight-membered cyclic ethers. Issue 14 (10th June 2020) - Wang, Hongkai; Zeng, Tianlong; Li, Xinhong; Wang, Songmeng; Xiao, Weiguo; Liu, Lingyan; Chang, Weixing; Li, Jing
Abstract : A cocatalyst-controlled divergent cascade cycloaddition reaction was developed for the synthesis of two different complex oxygen-containing heterocyclic compounds from arylalkynols and dioxopyrrolidienes in the presence of Au(i ) catalyst. Abstract : A cocatalyst-controlled divergent cascade cycloaddition reaction was developed for the synthesis of two different complex oxygen-containing heterocyclic compounds from arylalkynols and dioxopyrrolidienes in the presence of Au(i ) catalyst. Using two different cocatalysts, Ni(OTf)2 and ( rac )-phosphoric acid, two completely different products, spiroketals and oxa -bridged eight-membered cyclic ethers, were precisely constructed with high yields and good stereoselectivities, respectively. These methods feature simple and high efficiency, good chemoselectivity and mild conditions in one-pot.